Help when you need it: Perspectives of adults with T1D on the support and training they would have wanted when starting CGM. (October 2021) - Tanenbaum, Molly L.; Messer, Laurel H.; Wu, Christine A.; Basina, Marina; Buckingham, Bruce A.; Hessler, Danielle; Mulvaney, Shelagh A.; Maahs, David M.; Hood, Korey K.
Abstract: Aims: The purpose of this study was to explore preferences that adults with type 1 diabetes (T1D) have for training and support to initiate and sustain optimal use of continuous glucose monitoring (CGM) technology. Methods: Twenty-two adults with T1D (M age 30.95 ± 8.32; 59.1% female; 90.9% Non-Hispanic; 86.4% White; diabetes duration 13.5 ± 8.42 years; 72.7% insulin pump users) who had initiated CGM use in the past year participated in focus groups exploring two overarching questions: (1) What helped you learn to use your CGM? and (2) What additional support would you have wanted? Focus groups used a semi-structured interview guide and were recorded, transcribed and analyzed. Results: Overarching themes identified were: (1) "I got it going by myself": CGM training left to the individual; (2) Internet as diabetes educator, troubleshooter, and peer support system; and (3) domains of support they wanted, including content and format of this support. Conclusion: This study identifies current gaps in training and potential avenues for enhancing device education and CGM onboarding support for adults with T1D. Providing CGM users with relevant, timely resources and attending to the emotional side of using CGM could alleviate the burden of starting a new device and promote sustained device use.